Meningkatnya Marketing Performance Perusahaan Konstruksi Sebagai Dampak Hubungan Yang Signifikan Antara Digital Marketing Capabilities Terhadap Service Quality - Tobing, Wesly Tumbur ML; Zaenuri, Ahmad Zaenuri; Ramadhan, Adi Suryo (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The purpose of this research is to examine the role of service quality in creating a significant relationship between digital marketing capabilities and marketing performance in construction companies on the island of Java. The research method was carried out quantitatively by collecting data by distributing questionnaires through electronic forms and printed formats which were delivered directly to respondents where the respondents were directors working at contractor companies on the island of Java. The sampling technique was carried out purposively based on the distinction of directors who had worked for at least five years in positive companies on the island of Java. Based on these criteria, there are 211 company directories that have met these criteria. Data were analyzed using statistical software AMOS 22. The results showed that digital marketing capabilities had a positive and significant effect on service quality. Digital marketing capabilities have a positive and significant effect on marketing performance. Likewise, service quality has a positive and significant effect on marketing performance